(untitled) (Jurnal PGSD, 2025)
Leadership plays a crucial role in determining the direction and success of educational institution management, including financial matters. This study examines how leadership styles influence the planning and management of educational financing in educational institutions. A descriptive qualitative approach was employed, with data collected through questionnaires. The questionnaire instrument was developed based on indicators of transformational and transactional leadership styles, principles of educational financial management, and good governance values. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing/verification. The results of the study indicate that leaders who adopt participatory and communicative styles can effectively involve various stakeholders in the budgeting process, maintain transparency, and improve the efficiency of fund utilization. Good communication between leaders and staff also supports smooth collaboration and fosters a sense of ownership toward institutional financial policies. These findings suggest that the success of educational financial management is not solely dependent on the size of the budget, but also on the leadership quality in managing it. Therefore, enhancing the leadership capacity of educational leaders is essential to ensure that institutions operate more effectively and responsibly.